2018
DOI: 10.5306/wjco.v9.i4.60
|View full text |Cite
|
Sign up to set email alerts
|

Polyubiquitination inhibition of estrogen receptor alpha and its implications in breast cancer

Abstract: Estrogen receptor alpha (ERα) is detected in more than 70% of the cases of breast cancer. Nuclear activity of ERα, a transcriptional regulator, is linked to the development of mammary tumors, whereas the extranuclear activity of ERα is related to endocrine therapy resistance. ERα polyubiquitination is induced by the estradiol hormone, and also by selective estrogen receptor degraders, resulting in ERα degradation via the ubiquitin proteasome system. Moreover, polyubiquitination is related to the ERα transcript… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 112 publications
0
13
0
Order By: Relevance
“…Since ER alpha signaling is recognized as the driver pathway in the majority of breast cancer patients, the understanding of dysregulation of ER alpha signaling is of utmost importance. Recent studies have shown that several kinds of posttranslational modifications involved in ER alpha stability could contribute to amplified ER alpha signaling and tamoxifen resistance 14,15 . Several E3 ligases are shown to promote ER alpha signaling through stabilizing ER alpha protein, such as RNF31, SHAPRIN, and RNF8 7,16,17 .…”
Section: Introductionmentioning
confidence: 99%
“…Since ER alpha signaling is recognized as the driver pathway in the majority of breast cancer patients, the understanding of dysregulation of ER alpha signaling is of utmost importance. Recent studies have shown that several kinds of posttranslational modifications involved in ER alpha stability could contribute to amplified ER alpha signaling and tamoxifen resistance 14,15 . Several E3 ligases are shown to promote ER alpha signaling through stabilizing ER alpha protein, such as RNF31, SHAPRIN, and RNF8 7,16,17 .…”
Section: Introductionmentioning
confidence: 99%
“…Whilst ER is produced through transcription and protein synthesis, changes to ER degradation kinetics is the major factor determining ER levels. In BCa, there is an imbalance between the rate of transcription, synthesis and degradation of the ER leading to increased ER stability and thus activity [45]. The half-life of the ER differs significantly depending on estrogen exposure.…”
Section: Estrogen Receptor Turnovermentioning
confidence: 99%
“…Monoubiquitylation increases the stability and transcriptional activity of the receptor, whilst further addition of ubiquitin, polyubiquitylation, targets the protein for degradation by the UPS [53]. Some proteins have an inhibitory effect on ubiquitylation which leads to increased stability of the ER associated with ET resistance, broadly classified as coactivators, E3 ligases, kinases and scaffold proteins [45].…”
Section: Ubiquitylationmentioning
confidence: 99%
See 1 more Smart Citation
“…Molecular aspects of ERα-mediated transcriptions include allosteric mechanisms related to the intracellular traffics of the receptor and cofactor recruitments [8,9,[45][46][47][48][49][50][51]. These events analyzed in details in Sections 5-7 are briefly described here under to stress their importance to satisfy homeostasis or evolution.…”
Section: Factors Implicated In the Irreversible Character Of Erα-medimentioning
confidence: 99%